Use of one-bottle adhesive as an intermediate bonding layer to reduce sealant microleakage on saliva-contaminated enamel - Hebling, Josimeri [UNESP]; Feigal, Robert J. (My University, 2000)
Purpose: To evaluate the influence of three different adhesives, each used as an intermediary layer, on microleakage of sealants applied under condition of salivary contamination. Materials and Methods: Six different experimental conditions were compared, 3 with adhesives and 3 without. After prophylaxis and acid etching of enamel, salivary contamination was placed for 10 s. In Group SC the sealant was applied after saliva without bonding agent and then light-cured. In Group SCA, after saliva, the surface was air dried, and then the sealant was applied and cured. In Groups ScB, SB and PB, a bonding agent (Scotchbond Dual Cure/3M, Single Bond/3M and Prime & Bond 2.1/Dentsply, respectively) was applied after the saliva and prior to the sealant application and curing. After storage in distilled water at 37°C for 24 hrs, the teeth were submitted to 500 thermal cycles (5°C and 55°C), and silver nitrate was used as a leakage tracer. Leakage data were collected on cross sections as percentage of total enamel-sealant interface length. Representative samples were evaluated under SEM. Results: Sealants placed on contaminated enamel with no bonding agent showed extensive microleakage (94.27% in SC; 42.65% in SCA). The SEM revealed gaps as wide as 20 μm in areas where silver nitrate leakage could be visualized. In contrast, all bonding agent groups showed leakage less than 6.9%. Placement of sealant with a dentin-bonding agent on contaminated enamel significantly reduced microleakage (P< 0.0001). The use of a bonding agent as an intermediary layer between enamel and sealant significantly reduced saliva's effect on sealant microleakage.
Keywords: adhesive agent; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; Bisphenol A Glycidyl Methacrylate; dentin bonding agent; Dentin Bonding Agents; fissure sealant; polymethacrylic acid derivative; Prime & Bond; resin cement; Scotchbond Dual Cure; single bond; water; analysis of variance; cementation; chemistry; comparative study; enamel; human; molar tooth; pathology; preventive dentistry; saliva; scanning electron microscopy; silver staining; surface property; thermodynamics; time; tooth disease; ultrastructure; Acid Etching, Dental; Adhesives; Analysis of Variance; Bisphenol A-Glycidyl Methacrylate; Comparative Study; Dental Bonding; Dental Enamel; Dental Leakage; Dental Prophylaxis; Dentin-Bonding Agents; Human; Microscopy, Electron, Scanning; Molar, Third; Pit and Fissure Sealants; Polymethacrylic Acids; Resin Cements; Saliva; Silver Staining; Statistics; Support, Non-U.S. Gov't; Surface Properties; Thermodynamics; Time Factors; Water